Analysis Circuit Devices GPS Tracker Application In Identifying Location Of Ants - Naralita T; Cucus A (International Conference on Engineering and Technology Development (ICETD), 2017)
Along with the use of transport which is needed to enable people to do their daily activities day.Transportation including the movement of people or goods from one place to another by use of avehicle driven by human or machine. Population in Indonesia there who does not have a personal vehicle because they largely use public transport / bus as transport there. Every public transport has adifferent route so as to make the old passenger waiting at the stop because they do not know the location of the bus. In GPS technology developments needed assistance to developing transportationtechnology. At present the application of the system location has been done by using various methods and approaches.Global Positioning System (GPS) is a system for determining the location on theearth's surface with the aid of alignment(synchronization) satellite